A new species of Phanerotoma Wesmael (Hymenoptera: Braconidae: Cheloninae) parasitoid of the carob moth in South Africa - Achterberg, Cornelis Van; Thackeray, Sean R.; Hill, Martin P. (Zootaxa, 2017)
A new species, Phanerotoma carobivora van Achterberg & Thackeray, sp. nov. is described from South Africa. It is a common endoparasitoid of the carob moth (Ectomyelois ceratoniae Zeller (Pyralidae) on pecan (Carya illinoinensis (Wangenh.) K. Koch) and citrus fruits in South Africa. Mean percentage of parasitism varied 2-30% between host plants and sampled localities.